The Hologenome of Haliclona fulva (Porifera, Demospongiae) Reveals an Abundant and Diverse Viral Community - García-Bonilla, Erika; Chaves-Moreno, Diego; Riaño-Pachón, Diego; Terán, Wilson; Acosta, Alberto; Junca, Howard (Frontiers in Marine Science, 2021)
Viruses are among the most abundant biological entities in the ocean, largely responsible of modulating nutrients fluxes and influencing microbial composition and functioning. In marine invertebrate holobionts like sponges and their associated microbiomes, little is known about virome composition. Here, we characterized the Haliclona fulva hologenome, an encrusting low-microbial abundance sponge found across the Western Mediterranean Sea (35-40 m of depth) producer of a large metabolic repertoire of bioactive compounds and harboring a distinct and stable associated microbiome. Assembled contigs from shotgun metagenome sequences obtained from H. fulva specimens were comprehensively analyzed regarding taxonomic and functional content revealing its remarkable and abundant viral community dominated by ssDNA virus. Viral families consistently detected in contigs are Circoviridae, Phycodnaviridae, Poxviridae, Herelleviridae, Mimiviridae, Microviridae, and notably the first reported encounter of Nanoviridae and Genomoviridae in Porifera, expanding their known host range. The relative abundance of inferred bacteriophages/prophages was low, suggesting that the prokaryotic community in this sponge has a limited host range and susceptibility. H. fulva showed a distinct viral composition supporting the general proposition of specific and coevolving viromes in marine holobionts.